2017
DOI: 10.1155/2017/7392891
|View full text |Cite
|
Sign up to set email alerts
|

Poly‐ε‐Caprolactone Microsphere Polymers Containing Usnic Acid: Acute Toxicity and Anti‐Inflammatory Activity

Abstract: Usnic acid (UA) has been studied by its pharmacological properties; however, it presents moderate toxicity, low solubility, and absorption by biological membranes. The aim of this study was to develop poly-ε-caprolactone microsphere polymers containing UA (UA-micro) and evaluate their acute toxicity and anti-inflammatory activity. The microspheres were prepared by multiple emulsion technique (water/oil/water) and characterized by the encapsulation efficiency, particle size, polydispersity index, and zeta poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 31 publications
(36 reference statements)
1
6
0
Order By: Relevance
“…No other adverse clinical symptoms were observed. These results further confirmed that our carbohydrate-based NPs did not cause long-term immunotoxicity, as such a toxicity could result in malaise and altered animal behavior, leading to body weight reduction …”
supporting
confidence: 81%
See 1 more Smart Citation
“…No other adverse clinical symptoms were observed. These results further confirmed that our carbohydrate-based NPs did not cause long-term immunotoxicity, as such a toxicity could result in malaise and altered animal behavior, leading to body weight reduction …”
supporting
confidence: 81%
“…These results further confirmed that our carbohydrate-based NPs did not cause long-term immunotoxicity, as such a toxicity could result in malaise and altered animal behavior, leading to body weight reduction. 33 In conclusion, we designed and synthesized a series of new NP systems having SPOE as the hydrophobic component. Our studies, especially the parallel studies with PLA and PCL-based NP systems, indicate that the carbohydrate-based polymers can largely mitigate the hydrophobicity-induced immunotoxicity; therefore, they may, as low immunotoxic biomaterials, find applications for various biomedical and clinical studies.…”
mentioning
confidence: 99%
“…In another study, the toxicity of encapsulated UA was evaluated in vitro on HEp-2 cell lines using the MTT method, confirming a reduction of toxicity, compared to free UA [71]. Other authors confirmed these results, including a study that, besides assessing an increase of the anti-inflammatory effects of UA-loaded polymeric microparticles, and also reported a marked reduction of acute toxicity [75].…”
Section: Encapsulation Of Ua In Nanoand Microparticlesmentioning
confidence: 74%
“…The left ear samples were processed for histological and histomorphometric evaluation, while the right ear samples were homogenized in 50 mM phosphate buffer containing 0.5% hexadecyltrimethylammonium bromide (HTAB) for the quantification of myeloperoxidase activity [ 21 ].…”
Section: Methodsmentioning
confidence: 99%